South African women's experience of the decision, procedure and recovery from "feticide" and late termination of pregnancy due to the presence of severe fetal abnormality: women's and health service providers' perspectives - Vorster, Angela Carol (Rhodes University, Faculty of Humanities, Department of Psychology)
Routine antenatal care, including sonography and genetic testing, assist healthcare providers in identifying the presence of severe fetal abnormality. In countries where it is legal, the option to abort such a pregnancy may be presented to the pregnant person. When abortion takes place after the thirteenth week of gestation, it is generally referred to as a late termination of pregnancy and may entail the induction of labour or caesarean section. In cases where termination of the pregnancy is decided upon, and the gestation is further than 21 weeks and six days, the feticide procedure is recommended in order to ensure stillbirth. The feticide procedure entails the injection of potassium chloride directly into the fetal heart in order to ensure fetal demise. Existing literature on "feticide" and late termination of pregnancy (LTOP) owing to fetal abnormalities mostly takes a medical or psychological perspective in researching these procedures. Within the South African context, there are very few studies on feticide and LTOP, with none of these studies (to date "“ 8 January 2023) taking a feminist approach. This paucity of research that takes into account power relations, structural inequality and factors that affect decision-making and choice is one of the reasons that this study was undertaken. The main research question focused on in this study is: What are South African women's experiences of feticide and late termination of pregnancy due to the presence of severe fetal abnormality, as related by the women themselves and the health service providers who perform the procedure or provide care? The sub-questions that initially drove the study were: How do the women relate their experience of the process of coming to the decision, undergoing and recovering from the procedure, and how do health service providers relate the experiences of these women? The methodological and theoretical framework employed in this research was a Feminist Social Constructionist approach to Grounded Theory. This reflexive, subjectivist, feminist lens encouraged awareness of the influence of gender, race, class and other structural and systemic factors on women's experiences within the two healthcare systems. Data collection entailed semi-structured interviews conducted with 12 women, who had undergone feticide and LTOP procedures between one and five years prior to the interviews, in either the public or private healthcare system in South Africa. Semi-structured interviews were also conducted with 13 healthcare providers. The providers included medical specialists and participants from the fields of clinical psychology, genetic counselling and nursing and were employed in public or private healthcare in South Africa. Data relevant to public healthcare users and providers were collected from one tertiary (academic) public healthcare hospital and data regarding private healthcare users and providers were collected from across South Africa. Women's constructions of their experiences of feticide and LTOP included stark contrasts between public and private healthcare users in South Africa, as well as women experiencing "no choice" and their voices being ignored or silenced. Healthcare providers' constructions were frequently contradictory, referring to women as having freedom of choice and their needs largely prioritised within the healthcare system, while the providers within the public healthcare system relayed their own frustrations and emotional burden due to systemic failures. Findings from women and providers' constructions were synthesised into a theoretical understanding of women's experiences of feticide and LTOP in South Africa, which is grounded in, and emergent from, the data. Women's experiences of feticide and LTOP in South Africa were conceptualised by framing the three phases of these experiences, namely the decision-making phase (I), undergoing the procedures and in-hospital recovery (phase II) and the recovery phase (III). The most prominent themes emerging in these phases included the schism between the public and private healthcare systems in South Africa, the lack of real choice women experience, as well as the silencing of women and providers with regard to feticide and LTOP. Underlying the three phases, and directly influencing the three prominent themes affecting women's experiences, were the underlying and insidious structural inequality that undermined reproductive justice with regard to women's decision-making, experiences of and recovery from feticide and LTOP.
Keywords: Feticide; Abortion; Late-term abortion; Fetus -- Abnormalities; Psychological trauma; Grief; Pregnancy loss